2018
DOI: 10.1093/tas/txy086
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of human-edible protein conversion efficiency, net protein contribution, and enteric methane production from beef production in the United States

Abstract: A model was developed to estimate beef’s contribution toward meeting human protein requirements using a summative model of net protein contribution (NPC) and methane production. NPC was calculated by multiplying the ratio of human-edible protein (HeP) in beef to the HeP in feedstuffs by the protein quality ratio (PQR). PQR describes the change in biological value of HeP that occurs when plant-derived HeP is converted to beef. An NPC > 1 indicates that the production system is positively contributing to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 28 publications
2
46
3
3
Order By: Relevance
“…These are not trivial components of the overall dairy system; Thoma et al (2013) attributed 13% of dairy farm greenhouse gas emissions to beef production, and Tichenor (2015) suggested that this may be an underestimate. Nevertheless, dietary strategies similar to those evaluated herein can also contribute to net HE protein production in beef systems (Baber et al, 2018), and it is likely that our comparisons would hold for net beef + milk production, assuming ECO diets were employed across a farm. Future studies employing a lifecycle assessment using our approach would provide a more comprehensive estimation of net production of HE nutrients by the dairy industry.…”
Section: Human-edible Nutrient Recoverymentioning
confidence: 99%
“…These are not trivial components of the overall dairy system; Thoma et al (2013) attributed 13% of dairy farm greenhouse gas emissions to beef production, and Tichenor (2015) suggested that this may be an underestimate. Nevertheless, dietary strategies similar to those evaluated herein can also contribute to net HE protein production in beef systems (Baber et al, 2018), and it is likely that our comparisons would hold for net beef + milk production, assuming ECO diets were employed across a farm. Future studies employing a lifecycle assessment using our approach would provide a more comprehensive estimation of net production of HE nutrients by the dairy industry.…”
Section: Human-edible Nutrient Recoverymentioning
confidence: 99%
“…En contraste con las cifras, comúnmente se arma que 1 kg de carne requiere 2,8 kg de alimento comestible para los rumiantes y 3,2 kg para monogástricos. Sin embargo, el valor proteico de los productos derivados del ganado es 19 % superior a la calidad del producto ingerido para producir esa proteína (Baber et al, 2018;Flachowsky et al, 2017). La producción de proteína de origen bovino es altamente eciente y se puede considerar como una fuente de alimento de alto valor biológico para los humanos.…”
Section: Mito 2 Las Vacas Ocupan Tierras Agrícolas Que Podrían Produunclassified
“…Los alimentos de origen animal tienen mayor contenido de proteína verdadera que los alimentos de origen vegetal y el valor biológico de la proteína animal es aproximadamente 1,4 veces mayor que el de la proteína vegetal (Baber et al, 2018;Flachowsky et al, 2017). Además, se cree que la cantidad y la calidad de la proteína ayudan a regular la ingesta de alimentos en humanos (y otros animales) y reducir o controlar la obesidad (Simpson & Raubenheimer, 2005).…”
Section: Mito 5 Las Dietas Vegetarianas Son Mejores Para El Ambienteunclassified
“…For example, Groenestein et al (2016) estimated that the quantity of feed N required to produce meat is greatest for beef (~5 kg N/kg meat) and least for broiler chickens (~2 kg N/kg meat). However, in contrast to non-ruminants, because most of the protein in the diets of the cow herd, grazing stocker cattle and finishing cattle is from human-non-edible protein sources, cattle production actually increases the value of low-quality grass, grain and by-product proteins to highquality human-edible protein sources (Baber et al 2018). Approximately 40-60% of the N consumed daily by feedlot cattle is excreted in urine with 20-30% of N consumed being excreted in faeces .…”
Section: The Need For Improved N Efficiencymentioning
confidence: 99%